2017
DOI: 10.1108/jeim-08-2015-0078
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of e-health applications acceptance

Abstract: Purpose The increasing importance of electronic health (e-health) has raised the significance of exploring the factors influencing the users’ acceptance of e-health applications. There has been an extensive usage of the technology acceptance model (TAM) in e-health applications acceptance research. However, not all TAM relationships are borne out in all the studies. There is a variation in predicted effects in several studies with different user type and application type. The purpose of this paper is to bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 123 publications
0
19
2
2
Order By: Relevance
“…Similar to previous studies that applied the TAM in the context of general mHealth applications [21,49,67,68], the current results emphasized that the users' perceived usefulness and perceived ease of use together significantly influenced their attitude toward using MMT services, which further affected their intention to use such services in the future. However, in contrast to the findings of some previous studies [21,[68][69][70], the present work found that users' perceived ease of use of MMT services did not have a significant influence on their perceived usefulness. This might be because users who have already experimented with MMT services do not regard ease of use as a major consideration when weighing possible benefits and risks brought by such services.…”
Section: Factors Influencing the Acceptance Of Mmt Applicationscontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to previous studies that applied the TAM in the context of general mHealth applications [21,49,67,68], the current results emphasized that the users' perceived usefulness and perceived ease of use together significantly influenced their attitude toward using MMT services, which further affected their intention to use such services in the future. However, in contrast to the findings of some previous studies [21,[68][69][70], the present work found that users' perceived ease of use of MMT services did not have a significant influence on their perceived usefulness. This might be because users who have already experimented with MMT services do not regard ease of use as a major consideration when weighing possible benefits and risks brought by such services.…”
Section: Factors Influencing the Acceptance Of Mmt Applicationscontrasting
confidence: 99%
“…Theoretically, this study validated the robustness of the TAM in predicting users' acceptance and adoption intention of MMT services. Compared with previous studies that focused on general eHealth and mHealth services [17,70], the current findings more precisely reflect the acceptance behavior for online medical treatment in the field of mHealth. Furthermore, the findings identified the significant influences of additional factors, such as technology anxiety, trust, privacy concerns, personalization, and interactivity, which highlight the necessity of extending the TAM by emphasizing these unique variables and features in the context of mHealth.…”
Section: Discussioncontrasting
confidence: 38%
“…54 The primary health care focus has been on electronic health records 55 and specific eHealth applications. 56 Other applications are relatively neglected. 54 , 57 …”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Therefore, it is strongly suggested to gather information from Covid-19 patients and physicians to investigate the effect of the e-health system on patient care and relationships between doctors and patients. As mentioned by Chauhan and Jaiswal (2017) sufferers and the local population developed diverse views and practices regarding the use and benefits of e-health systems. Second, the model was validated using data obtained in Pakistan, which could be considered a research constraint (Zhang, Rasheed, & Luqman, 2019).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%